Enhancing solar panel cooling efficiency: a study on the influence of nanofluid inclusion and pin fin shape during melting and freezing of phase change materials - Mustafa, Jawed; Alqaed, Saeed; Sajadi, S. Mohammad; Aybar, Hikmet Ş. (Frontiers in Energy Research, 2024)
The present article presents a 3D simulation of a solar thermal panel containing phase change materials (PCMs). Two pipes are devised in the panel, and several pin fins (PFs) are applied to each pipe. Organic PCMs are encapsulated in a compartment around the PFs and pipes. The variable is PF shape, which includes four types, i.e., square, rectangular, triangular, and circular. Nanofluid (NFD) is used within the pipes. The study is carried out transiently and continued until the stabilization of outlets. Utilizing an FEM method based on a weak form, namely Galerkin, to find a numerical solution for mathematical modeling. The artificial intelligent results indicate that using triangular, square, rectangular, and circular PFs provides the highest NFD temperature in the outlet, respectively. Circular PFs lead to a lower heat transfer coefficient (HC) compared to other PFs. The comparison between various PF shapes shows that the use of circular and triangular PFs results in the lowest and highest panel temperature, respectively. Moreover, the highest and lowest volume fraction of melting PCMs around the pipe is obtained through the use of triangular and circular PFs, respectively.